NEW TRENDS AND DEVELOPMENTS IN EDUCATIONAL TECHNOLOGY RESEARCH - MANJULA, Dr. V.S. (IJRDO -Journal of Computer Science Engineering, 2016)
Educational Technology research has moved through several stages of focusing at the beginningon the content to be learned, then on the format of instructional messages and, finally on theinteraction between computers and students. A great majority of the theses employed quantitativeparadigm, and qualitative studies made about one fourth of the total studies. The present paperreviews the research in technology-based learning environments in order to give both a historicalperspective on educational technology research and a view of the current state of this discipline.To conclude that 1) trends in educational technology research were forged by the evolution oflearning theories and the technological changes 2) a clear shift from the design of instruction tothe design of learning environments can be noticed 3) there is a positive effect of educationaltechnology on learning, but the size of the effect varies considerably 4) learning is much moredependent on the activity of the learner than on the quantity of information and processingopportunities provided by the environment. The most frequently investigated topics werecomputer-assisted instruction, alternative teaching and learning approaches, web-based learning,difficulties in integrating information technologies into educational practice, Internet-basedlearning, and distance education